Adsorção de cafeína e paracetamol em carvão ativado funcionalizado - Couto Júnior, Osório Moreira (2014)
Due to great technological advances and to the resulting generation of residues contaminating the soil, water and air of our planet, it has become necessary to develop innovative lines of research for the treatment of industrial pollutants. One such line of research is adsorption, a process that has been used as an alternative for the treatment of effluents containing drugs. The present work was focused on the removal of caffeine and paracetamol in aqueous solutions by adsorption on activated carbon, without functionalization, functionalization in nitric acid and inert atmosphere. The lab-made carbons prepared from babassu and dendê coco and commercially available activate carbon, indicating that the laboratory carbons can be considered as alternatives for water treatment. The characterizations were carried point of zero charge, adsorption/desorption of N2, and elemental analysis. The adsorption capacity of these activated carbons was evaluated, and among vegetal carbons, the babassu functionalization in inert atmosphere was the the most capacity of approximately 102 mg/g and 187 mg/g for paracetamol e cafeína, caffeine and paracetamol, respectively. The adsorption kinetics of caffeine and paracetamol presented a better adjustment to the pseudo-second order kinetic equation, the pseudo-first orde weas also evaluated. Indicating that diffusion of molecules through the boundary layer is the rate limiting step for adsorption and chemisorption occur. The equilibrium results presented a better adjustment to the Freundlich and Langmuir model and allow to confirm the results obtained in the kinetic assays. In the analysis of various isotherms were applied different equations by non-linear adjustments. Error functions were evaluated in order to standardize the degrees of freedom, allowing comparing the results obtained by the models. The study of the influence of water hardness in the adsorption caffeine and paracetamol, functionalized carbons in an inert atmosphere, showed a significant interference of the ions Ca+2 e Mg+2 in the adsorption process, decreasing the efficiency and increasing the rate of removal. To verify the ability of the paracetamol desorption, the parameters evaluated in the desorption of the paracetamol were contact time, and initial concentration of regenerants, and products used to perform the desorption water, NaOH, methyl alcohol, and ethyl alcohol. For the representation of the dynamic of adsorption in fixed bed column, was used Silva (2001) model that considered the diffusion in external film, and diffusion particles as controller steps of mass transfer. The results showed the model represented properly the dynamic of adsorption in all of the cases investigated.